2020
DOI: 10.1158/1078-0432.ccr-19-2299
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Activity of JNJ-7957, a Novel BCMA×CD3 Bispecific Antibody for the Treatment of Multiple Myeloma, Is Potentiated by Daratumumab

Abstract: Purpose: Multiple myeloma (MM) patients with disease refractory to all available drugs have a poor outcome, indicating the need for new agents with novel mechanisms of action.Experimental design: We evaluated the anti-MM activity of the fully human BCMAÂCD3 bispecific antibody JNJ-7957 in cell lines and bone marrow (BM) samples. The impact of several tumor-and host-related factors on sensitivity to JNJ-7957 therapy was also evaluated.Results: We show that JNJ-7957 has potent activity against 4 MM cell lines, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 46 publications
3
52
0
Order By: Relevance
“…Because of the high single agent activity and good tolerability profile of the BCMA-targeting bispecific antibodies, these agents are ideal components of a highly effective combination therapy. We showed that the direct combination of teclistamab with the CD38-targeting antibody daratumumab enhanced MM cell lysis in an additive fashion [14]. In addition, the activity of teclistamab was significantly enhanced in bone marrow samples obtained from patients with prior daratumumab treatment.…”
Section: Future Developments Combination Treatmentmentioning
confidence: 87%
See 2 more Smart Citations
“…Because of the high single agent activity and good tolerability profile of the BCMA-targeting bispecific antibodies, these agents are ideal components of a highly effective combination therapy. We showed that the direct combination of teclistamab with the CD38-targeting antibody daratumumab enhanced MM cell lysis in an additive fashion [14]. In addition, the activity of teclistamab was significantly enhanced in bone marrow samples obtained from patients with prior daratumumab treatment.…”
Section: Future Developments Combination Treatmentmentioning
confidence: 87%
“…Furthermore, teclistamab-mediated tumor cell lysis was superior when T-cells obtained from patients treated with daratumumab were used, compared to T-cells from daratumumab naïve MM patients [14]. This positive effect of daratumumab on the ability of teclistamab to kill MM cells, is probably related to the immune stimulating effects of daratumumab, which include the elimination of immune suppressor cells, induction of T-cell expansion, and increase in T-cell killing capacity [14,[21][22][23]. These data form the rationale for the ongoing phase 1 TRIMM study, which evaluates the efficacy of teclistamab plus daratumumab.…”
Section: Future Developments Combination Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, many bispecific Abs target BCMA on MM cells and CD3 on T cells or CD16 on NK effector cells. EM801 [ 30 ], BCMA-TCB2/EM901 (CC-93269) [ 30 , 89 ], JNJ-7957 [ 101 ] and TNB-383B [ 60 , 102 , 103 ] all target CD3 on T cells and BCMA on MM cells. AFM26, a tetravalent bispecific Ab targeting BCMA on MM cells and CD16A on NK cells, showed potent NK-cell-medicated ADCC [ 104 ].…”
Section: Immunotherapies Targeting Bcmamentioning
confidence: 99%
“…Target antigen expression is an important factor for target recognition and effector function by mAbs (213). There is considerable heterogeneity in expression of target antigens between MM patients (16,(213)(214)(215)(216)(217)(218). Patients with low levels of target antigen on the tumor cell surface are at increased risk of treatment failure (213).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%